Variety of Pests and Arthropods in Organic and Non-organic Rice Cultivation in South Sumatera - Ardi Asroh; Abu Umayah; Yulia Pujiastuti (Science and Technology Indonesia, 2018)
The system of cropping pattern and the use of fertilizer will be different to the diversity of pests and arthropods in paddy fields. The objective of this research is to determine the pest and arthropod pests in non-organic and organic paddy in paddy fields. The applied method is the plant observations that attacked pests by using 1 ha of organic paddy field and 1 ha of non-organic paddy field. The catching arthropods is the way to observed the insects by using insect nets, trap holes, yellow trays and light traps and analyzing the result by using the Shannon-Wiener equation. This research was undertaken on April 2016 to August 2016 in Sumber Suko village, BK. VIII, Gumawang district, regency of Ogan Komering Ulu east, South Sumatera. The result of this research pointed out that the variety of pest paddy crops is relatively diverse both in non-organic and organic paddy. The abundance and variety of arthropods in organic agriculture is higher at 1.39 than non-organic agriculture at 0.87 so it can affect the extent of pest attacks on organic paddy. The ecosystem of organic paddy. The ecosystems of organic paddy is more complex in the diversity of arthropods and the abundance of microorganisms than non-organic paddy systems.